Chloroplast Glutamine Synthetase, the Key Regulator of Nitrogen Metabolism in Wheat, Performs Its Role by Fine Regulation of Enzyme Activity via Negative Cooperativity of Its Subunits - Németh, Edit; Nagy, Zoltán; Pécsváradi, Attila (Frontiers in Plant Science, 2018)
Glutamine synthetase (GS) is of central interest as the main route of ammonia assimilation in plants, and as a connection point between the organic and inorganic worlds. Even though GS activity is critical for producing high yields of crop plants, the autoregulation of substrate consumption of wheat GS remained unknown until now. Here we show kinetic evidence, that the chloroplast localized GS isoform (GS2) of wheat (Triticum aestivum L. cv. Jubilejnaja-50) takes place at the carbon-nitrogen metabolic branch point, where it is a mediator, and its enzymatic activity is regulated in a negatively cooperative allosteric manner. We have discovered that GS2 activity is described by a tetraphasic kinetic curve in response to increasing levels of glutamate supply. We constructed a model that explains the kinetic properties of glutamate consumption and this unique allosteric behavior. We also studied the subunit composition of both wheat leaf GS isoenzymes by a combination of two dimensional gel electrophoresis and protein blotting. Both leaf isozymes have homogeneous subunit composition. Glutamate is both a substrate, and an allosteric regulator of the biosynthetic reaction. We have concluded on the basis of our results and previous reports, that wheat GS2 is probably a homooctamer, and that it processes its substrate in a well-regulated, concentration dependent way, as a result of its negatively cooperative, allosteric activity. Thus GS2 has a central role as a regulator between the nitrogen and the carbon cycles via maintaining glutamine-glutamate pool in the chloroplast on the level of substrates, in addition to its function in ammonia assimilation.